PERAN BUDAYA ORGANISASI DAN MOTIVASI INDIVIDU PADA PRAKTIK BERBAGI PENGETAHUAN - Anwar Mansyur; Suhana Suhana (Universitas Ahmad Dahlan, 2023)
Batik is a traditional cloth of Indonesia made by writing or waxing it on the cloth. Information related to batik products will be very crucial because this product has been acknowledged as World cultural heritage by UNESCO. This study aims to examine the influence of culture and motivation on the practice of sharing knowledge about batik. The object of this research was Batik artisans and entrepreneurs in Yogyakarta. The number of samples used was 237 respondents with a purposive sampling technique. The data were analyzed by statistical testing using the SEM test with the AMOS program. The results showed that organizational culture positively influences the practice of sharing knowledge. Furthermore, organizational culture has a positive role in motivating batik artisans and entrepreneurs. The following finding is that intrinsic motivation influences someone to share knowledge, while extrinsic motivation does not influence batik artisans and entrepreneurs to carry out knowledge-sharing activities.